FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK (Studi Empirik Pada Industri Perbankan Di Bursa Efek Indonesia Tahun 2010-2013) (Students' Journal of Accounting and Banking, 2015)
This study aimed to analyze the influence of the Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR), Non Performing Loan (NPL), Debt Equity Ratio (DER) to the return on assets (ROA) at Commercial Bank. The population in this study is a commercial bank in Indonesia, which is listed on the Indonesia Stock Exchange (IDX) and still in operation during the years 2010 to 2013. Commercial banks may include state-owned banks, national private banks and foreign banks and mix. The sample in this study was obtained by the method of purposive sampling that samples taken based on the criteria used by researchers. Samples taken as many as 24 commercial banks. Data company then tested by means of multiple linear regression analysis. The results of this study addressed that the Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR) and no significant negative impact on the return on assets (ROA). While the Non Performing Loan (NPL) is not significant and positive effect Debt Equity Ratio (DER) and a significant negative effect on the return on assets (ROA). Thus the higher the Debt Equity Ratio (DER) shows the composition of total debt greater than the total equity and impact the greater the burden on companies to outsiders that will affect the profitability of banks.Keywords: Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR), Non Performing Loan (NPL), Debt Equity Ratio (DER), Return On Assets (ROA)